Double-edged sword : nuclear diplomacy in unequal conflicts : the United States and China, 1950-1958 - Soman, Appu Kuttan, 1951- (Praeger studies in diplomacy and strategic thought., 2000)
This work explores the efficacy of nuclear diplomacy and the consequences of American nuclear-brinkmanship, via a study of the political and diplomatic role of America's nuclear capabilities in conflicts with a non-nuclear China during the Korean War and the Taiwan Strait Crises.